Isolation and Molecular Identification of Nitrate-Reducing Bacteria from Swiftlet Houses in Sumedang, West Java - Ningrum, Siti Gusti; Novik Nurhidayat; Titin Yulinery; Evi Triana; Olan Rahayu Puji Astuti Nussa; Ady Kurnianto (IPB University, 2025)
Edible bird‘s nest is an important export commodity that is currently of concern to the Indonesian government. One of the requirements for exporting edible bird’s nest to the People's Republic of China is that this product must meet the requirements for nitrite content in the product below 30 ppm. This nitrite contamination can be obtained from the results of nitrogen metabolism from nitrifying bacteria. However, information on nitrite-reducing bacteria in swiftlet houses has never been reported and is urgent in controlling nitrifying bacteria in swiftlet houses. The presence of nitrite-reducing bacteria needs to be identified to prove the presence of these bacteria in swiftlet houses that have the potential to contribute to nitrite contamination in edible bird’s nest. This study aims to isolate nitrate-reducing bacteria in an effort to control nitrite using bacteriophages in the future. This study targeted nitrate-reducing bacteria collected from environmental samples (waste, feces, pond water, artificial pond water, soil, swiftlet eggshells, white edible bird’s nest (Aerodramus fuciphagus), black bird’s nest (Aerodramus maximus)) (n=40) from two different swiftlet houses in Sumedang, West Java, Indonesia. All isolates collected were subjected to a series of microbiological tests, phenotypic characterization (Gram staining, morphology, sugar fermentation ability, enzymes, etc.) and genotyping by PCR amplification and 16S rDNA gene sequencing. Raw sequencing data were analyzed using DNASTAR® software for DNA sequence alignment and phylogenetic tree construction. In the present work, four bacteria species were identified, including Priestia megaterium, Pseudomonas putida, Stenotrophomonas maltophilia, and Proteus terrae. To our knowledge, this study is the first report of nitrate-reducing bacteria isolated from birdhouses.